2022
DOI: 10.1039/d2tc00005a
|View full text |Cite
|
Sign up to set email alerts
|

Novel butterfly-shaped AIE-active pyrrolopyrrole aza-BODIPYs: synthesis, bioimaging and diamine/polyamine detection

Abstract: Constructing novel near-infrared (NIR) fluorophores with aggregation-induced emission (AIE) character is of particular interest but remains challenging. In this work, we linked two propeller-shaped alkoxyl-substituted tetraphenylethylene (TPE) to the short...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…36,37 For instance, the core of BODIPY, pyrrolopyrrole aza-BODIPY (PPAB), and pyrrolopyrrole cyanine (PPCy) was susceptible to being attacked by nucleophiles such as a base, hydrazine, and organic amine. 38–42 Herein, by virtue of the nucleophilicity of the primary amine group in SEM, our findings indicated that PPCy-1 showed a sensitive response toward SEM through a chromophore reaction (Scheme 1C). This strategy for detecting SEM has the following advantages.…”
Section: Introductionmentioning
confidence: 79%
“…36,37 For instance, the core of BODIPY, pyrrolopyrrole aza-BODIPY (PPAB), and pyrrolopyrrole cyanine (PPCy) was susceptible to being attacked by nucleophiles such as a base, hydrazine, and organic amine. 38–42 Herein, by virtue of the nucleophilicity of the primary amine group in SEM, our findings indicated that PPCy-1 showed a sensitive response toward SEM through a chromophore reaction (Scheme 1C). This strategy for detecting SEM has the following advantages.…”
Section: Introductionmentioning
confidence: 79%
“…270 In another example, NIR-emitting fluorophore C43 bearing pyrrolopyrrole aza-BODIPY core was found to show selective detection of diamines and biogenic amines via a dark green-to-yellow colour change, and the turn-on of bright orange fluorescence, due to B–N bond cleavage followed by fast hydrolysis to form smaller conjugated molecules. 271…”
Section: Sensing For Environmental Monitoring and Food Safetymentioning
confidence: 99%
“…fluorescence, due to B-N bond cleavage followed by fast hydrolysis to form smaller conjugated molecules. 271 Amines are generally basic. Therefore, fluorescent amine sensors can be rationally designed to involve deprotonation by basic amine to trigger optical changes.…”
Section: Volatile Aminesmentioning
confidence: 99%
“…Usually, organic amines are highly toxic, harmful, colorless, and without chromogenic groups, which renders them difficult to be directly differentiated through visual inspection 3 5 . Thereinto, polyamines are implicated in diverse functional applications, such as analytical detection 6 , drug development 7 , chemotherapy 8 10 , and biological regulation 11 , which makes the determination of polyamines particularly important 12 , 13 , especially in synthetic polyamines detection. For example, the melamine scandal, as an infant-formula milk scandal that results in the hospitalization of tens of thousands of children and even a few deaths 14 , has alarmed the safety of global food chains 15 .…”
Section: Introductionmentioning
confidence: 99%